Co-occurrence of opisthorchiasis and diabetes exacerbates morbidity of the hepatobiliary tract disease - Chaidee, Apisit; Onsurathum, Sudarat; Intuyod, Kitti; Pannangpetch, Patchareewan; Pongchaiyakul, Chatlert; Pinlaor, Porntip; Pairojkul, Chawalit; Ittiprasert, Wannaporn; Cochran, Christina J.; Mann, Victoria H.; Brindley, Paul J.; Pinlaor, Somchai (PLOS Neglected Tropical Diseases, 2018)
Author summary Infection with the food-borne liver fluke Opisthorchis viverrini frequently causes bile duct cancer, a prominent public health concern in the greater Mekong sub-region countries. In like fashion, diabetes mellitus is a major public health problem in this region and worldwide. The interrelationships of these two conditions were investigated in hamsters and in tissue cultures of human liver cells. Liver fluke infection exacerbated diabetes-related disease in the liver and bile ducts in hamsters and in the cultured cells. The findings of this investigation revealed that infection with liver fluke parasites during diabetes leads to more serious disease in the liver than is due to either condition alone.